A descriptive study on the influence of wheelchair design and movement trajectory on the upper limbs’ joint angles - Bertolaccini, Guilherme [UNESP]; Sandnes, Frode; Filho, Idnei [UNESP]; Paschoarelli, Luis [UNESP]; Medola, Fausto [UNESP] (Springer Nature, 2018)
Several aspects of the design and configuration of manual wheelchairs have been indicated as factors that influence the biomechanics of the upper limbs during manual propulsion. From a kinematic point of view, the angles of the shoulder and elbow are particularly important, as they can reveal potentially harmful joint positions as well as providing information that can complement the analysis of the performance of the propulsion technique. This study investigated the influence of two different designs of manual wheelchairs (rigid frame and foldable frame) on the shoulder and elbow angles during manual propulsion in straightforward and turning trajectories. Eleven subjects without disabilities performed a propulsion protocol comprising a 15-m straightforward sprint and a 2-m radius turn in both clockwise and anticlockwise direction. During the propulsion tests, data of shoulder and elbow angles were collected using accelerometers. The results revealed that manual propulsion with a rigid frame wheelchair may provide more protection as it was related to lower maximum angles of shoulder extension and abduction and elbow flexion-extension range of motion in comparison with the foldable frame chair. Providing a wheelchair design and configuration that reduces the biomechanical risks and increases efficiency may benefit the users’ safety, independence and satisfaction with their wheelchairs.
Keywords: Assistive technologies; Biomechanics; Design; Joint angles; Wheelchairs